An Examination of Compositional Writing Instruction in Irish Primary Schools - Willoughby, Karen (Trinity College Dublin, 2007)
Recent government reports highlight potential delays in the implementation of the revisions to writing instruction outlined in the 1999 English Curriculum for primary schools. Although delays appear to exist, the nature and origin of these delays has yet to be examined in explicit detail. The overall aim of this study is to conduct an in-depth examination of the approaches to compositional writing instruction used in Irish primary schools.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Irish Primary Schools; Compositional Writing Instruction